Revisiting liver disease progression in HIV/HCV‐coinfected patients: the influence of vitamin D, insulin resistance, immune status, IL28B and PNPLA3. (26th June 2014) - Mandorfer, Mattias; Payer, Berit A.; Schwabl, Philipp; Steiner, Sebastian; Ferlitsch, Arnulf; Aichelburg, Maximilian C.; Stättermayer, Albert F.; Ferenci, Peter; Obermayer‐Pietsch, Barbara; Grabmeier‐Pfistershammer, Katharina; Trauner, Michael; Peck‐Radosavljevic, Markus; et al.
Abstract Background & Aims To perform a comprehensive study on independent modulators of liver fibrosis progression and determinants of portal pressure considering immune status, insulin resistance (IR), serum 25‐hydroxyvitamin D (25(OH)D) levels, genetic variants of patatin‐like phospholipase domain‐containing protein 3 (PNPLA3) and interleukin 28B (IL28B) in a thoroughly documented cohort of HIV/hepatitis C‐coinfected (HIV/HCV) patients. Patients & Methods 25(OH)D deficiency (25(OH)DDEF), IR and low CD4+ T‐lymphocyte nadir (lowCD4NAD) were defined as 25(OH)D <20 ng × ml−1, HOMA‐IR >2 and CD4nadir <200 cells × μl−1 respectively. Liver fibrosis progression rate (FPR) was calculated as METAVIR F units divided by the number of years since HCV infection. Patients with a FPR > median FPR were assigned to the highFPR group. Results Among 86 HIV/HCV, the median FPR was 0.167 units × years−1. While the prevalence of prior alcohol abuse, lowCD4NAD and 25(OH)DDEF was higher among highFPR patients, the prevalence of IR was comparable. The association between 25(OH)DDEF and FPR was confirmed in a subgroup of patients with METAVIR stage F0/F1/F2 in which 25(OH)D levels are not affected by the severity of liver disease. The distribution of IL28B C/C and PNPLA3 non‐C/C was similar, while PNPLA3 G/G was exclusively observed in highFPR patients. LowCD4NAD (OR: 2.95; 95% CI: 1.05–8.24; P = 0.039) and 25(OH)DDEF (OR: 5.62; 95% CI: 2.05–15.38; P = 0.001) were independently associated with highFPR and showed an additive effect. Portal pressure correlated with prior alcohol abuse, HCV‐genotype 3, CD4+ nadir and 25(OH)D levels. Conclusions Two potentially modifiable factors, CD4+ nadir and 25(OH)D levels, were both independent modulators of liver fibrosis progression and determinants of portal pressure. Further studies are warranted to assess the relevance of PNPLA3 for FPR in HIV/HCV.